Negotiating the implementation of peacebuilding: a challenge for the transition to peace and democracy - Lisa Groß (Deutsches Institut für Entwicklungspolitik (DIE), 2017)
The success of peacebuilding not only depends on the effective negotiation of peace agreements, but essentially also on how negotiations fare during the practical implementation of peacebuilding policies on the ground. Negotiations are thus a central part of the daily business of United Nations (UN) peacebuilding operations. International actors play an important part in these negotiations, not only as facilitators between conflict parties, but as an own party with the political agenda to promote peace and democracy. Yet the impact of negotiations between international actors and domestic elites on the success of peacebuilding has only received limited attention so far. Given the mixed success of UN peacebuilding operations in promoting peace and democracy in post-conflict contexts, this neglect is a missed opportunity to search for avenues that could make peacebuilding more sustainable. This Briefing Paper therefore engages with the role of negotiations in implementing peacebuilding policies and their impact on peacebuilding success. It particularly scrutinizes the challenges that international actors confront during a negotiation process and which constrain the prospects of reaching proclaimed goals of peace and democracy. Several aspects of negotiation processes either limit international actors in pushing through their demands or provide domestic elites with ample leeway to pursue interests not necessarily aligned with peacebuilders' goals. These challenges to negotiation processes need to be carefully taken into account when planning a peacebuilding intervention. The findings of this Briefing Paper rest on a fine-grained process tracing of external-domestic interactions in four policy fields at the local level in Kosovo. The following messages need to be kept in mind regarding the role of negotiations in peacebuilding: Peacebuilding is a constant negotiation process. Negotiations do not stop after the conclusion of a peace agreement; peacebuilding goals and practice continue to be negotiated at every step of policymaking. Thus the success of peacebuilding also depends on how negotiations fare during implementation. During such negotiation processes particular challenges arise for international actors vis-à-vis domestic actors: the reconciliation of the diverging goals of peacebuilders and domestic elites; mutual dependencies on both sides; the balance between flexibility and long-term strategies; and the selectivity of international engagement. In light of these challenges, international actors need to: Be aware of the need for compromise but make sure that compromises do not undermine overall peacebuilding goals. Issues for negotiation need to be selected strategically with a view to ensuring the best outcome of a peacebuilding policy. Be aware of the need for contingency planning while finding a balance between flexibility and strategic long-term thinking. Fast-changing security environments may require strategic readjustment, but arbitrary ad hoc changes in priorities must be avoided.
Keywords: 330